Effects of bromopride on expression of metalloproteinases and interleukins in left colonic anastomoses: an experimental study - Silva,S.M. (2014)
Anastomotic dehiscence is the most severe complication of colorectal surgery. Metalloproteinases (MMPs) and interleukins (ILs) can be used to analyze the healing process of anastomosis. To evaluate the effects of bromopride on MMP and cytokine gene expression in left colonic anastomoses in rats with or without induced abdominal sepsis, 80 rats were divided into two groups for euthanasia on the third or seventh postoperative day (POD). They were then divided into subgroups of 20 rats for sepsis induction or not, and then into subgroups of 10 rats for administration of bromopride or saline. Left colonic anastomosis was performed and abdominal sepsis was induced by cecal ligation and puncture. A colonic segment containing the anastomosis was removed for analysis of gene expression of MMP-1α, MMP-8, MMP-13, IL-β, IL-6, IL-10, tumor necrosis factor-α (TNF-α), and interferon-γ (IFN-γ). On the third POD, bromopride was associated with increased MMP-1α, MMP-13, IL-6, IFN-γ, and IL-10 gene expression. On the seventh POD, all MMP transcripts became negatively modulated and all IL transcripts became positively modulated. In the presence of sepsis, bromopride administration increased MMP-8 and IFN-γ gene expression and decreased MMP-1, TNF-α, IL-6, and IL-10 gene expression on the third POD. On the seventh POD, we observed increased expression of MMP-13 and all cytokines, except for TNF-α. In conclusion, bromopride interferes with MMP and IL gene expression during anastomotic healing. Further studies are needed to correlate these changes with the healing process.